2004
DOI: 10.1002/ptr.1348
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological evaluation of the essential oils of different Melaleuca species

Abstract: The essential oils of the fresh leaves of M. ericifolia, M. leucadendron, M. armillaris and M. styphelioides were isolated by a hydrodistillation method and analysed by a gas chromatography/mass spectrometry (GC/MS) technique. The essential oil of M. ericifolia contained methyl eugenol (96.84%) as a major constituent, whereas M. leucadendron was rich in 1,8-cineole (64.30%). The essential oil of M. armillaris was rich in 1,8-cineole (33.93%) followed by terpinen-4-ol (18.79%), whereas M. styphelioides was rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
100
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(107 citation statements)
references
References 21 publications
3
100
0
4
Order By: Relevance
“…In addition, Cuban folk medicine information also shows several other medicinal uses for these plants, including antihelminthic, antidysenteric and antiherpetic action (Roig 1974). Similarly, the anti-infective properties of these plants have been confirmed by several other research groups (Caceres et al 1990, Franssen et al 1997, Farag et al 2004). …”
supporting
confidence: 57%
See 1 more Smart Citation
“…In addition, Cuban folk medicine information also shows several other medicinal uses for these plants, including antihelminthic, antidysenteric and antiherpetic action (Roig 1974). Similarly, the anti-infective properties of these plants have been confirmed by several other research groups (Caceres et al 1990, Franssen et al 1997, Farag et al 2004). …”
supporting
confidence: 57%
“…This extract can be considered as relatively-non toxic with a CC 50 value of 20 µg/ml. About antibacterial activity, Hussein et al (2007) reported activity of Melaleuca ericifolia leaves extract whereas Farag et al (2004) showed that all essential oils extracted from four different Melaleuca species, including M. leucadendron, vary in composition but possess antibacterial and antifungal activities. We detected some activity against M. canis (IC 50 = 13 µg/mL).…”
mentioning
confidence: 99%
“…These attributes prompted us to investigate the hepatoprotective activity of an ellagitannin-rich plant belonging to the Myrtaceae family, namely Melaleuca styphelioides Sm. Previous studies have reported that various Melaleuca species are rich sources of bioactive compounds, such as volatile oils (Farag et al, 2004), ellagitannins (Yoshida et al, 2008), and flavonoids . Different Melaleuca species are used in the traditional medicine for the treatment of several ailments (Southwell & Robert, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Different Melaleuca species are used in the traditional medicine for the treatment of several ailments (Southwell & Robert, 1999). Several studies have proved the strong in vitro antioxidant activity of various Melaleuca species (Farag et al, 2004;Kim et al, 2004). M. styphelioides, known as prickly-leaf tea tree, is a small to medium-sized ornamental tree (Byrnes, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Its antimicrobial effects have been widely studied. The plant has been used for controlling the growth of Escherichia coli and Salmonella (2)(3)(4)(5). The plant's extract also has anti-helicobacter activities (6).…”
Section: Introductionmentioning
confidence: 99%